Vaderlandse weelde op de kaart gezet. Belgische botanici, wetenschappelijke ijver en nationale motieven - Stynen, A. (BMGN - Low Countries Historical Review, 2006)
Andreas Stynen, Native wealth charted. Belgian botanists, scientific zeal and patriotic motivesThis article analyses the importance of patriotic motives in nineteenth-century Belgian botany, without reducing the study of indigenous plants to a vehicle of aggressive, blatantly biased chauvinism. Different forms of more subtle nationalism enabled Belgian field botanists to define their activities as a mature and internationally respected field among the natural sciences. Four different phases can be discerned. During the period of Austrian and French domination, botany was first and foremost a means to economically enrich the state, by reducing its dependence on imports. After Belgian independence (1830), striving for utility was increasingly overshadowed by a longing for completeness: field trips were fuelled by a desire to collect and chart all Belgian species. From 1860 onwards, individual species mattered less than the geobotanical regions: the national territory was discovered to offer a rich variety of landscapes. The popularity of laboratories at the end of the century threatened to dismiss field botany as merely amateurish, but an ecological approach to the national vegetation, combined with explicit pleas for the protection of Belgian’s natural wealth, provided the impetus for a new round of research. This article is part of the special issue 'Landschap, natuur en nationale identiteit'.